A study of Eagle’s syndrome in CMS-TH Bharatpur - Shah, DK; Ganguly, SN; Reddy, NS (Journal of College of Medical Sciences-Nepal, 2015)
Objective To study the common symptoms and outcome of surgical treatment of Eagle’s syndrome Methods A total of 22 cases were studied prospectively in both sexes from January 2008 to December 2010, in Department of ENT-HNS College Of Medical Sciences-Teaching Hospital, Bharatpur, Nepal. Patients with symptomatic styloid process were clinically palpated at tonsillar fossa and finally sent for X-ray styloid process. Patients underwent intra-oral tonsillectomy with styloidectomy. Post-operative improvement was analysed by follow up at one three and six months interval. Results Most common age group was 30-40 years (63.63%) with female dominance (M:F=1:4.5). The most frequent symptoms were pain in throat (29.62%), referred pain in ear (20.37%), pain in anterior triangle in neck (24.07%), foreign body sensation in throat (14.81%) and difficulty in swallowing (11.11%). Fifty nine percent of patients were having symptoms for last two to four years and 50% were on medication for last one to two years. All the patients underwent styloidectomy through intra-oral route. (63.63%) patients became symptom free and 13.63% didn’t show improvement even after operation. Conclusion Eagle’s syndrome is common in young females with various atypical presentations. Dull/throbbing or radiationg throat pain and pain in anterior triangle of the neck are common presentations. Diagnosis is done simply by palpating the tonsillar fossa. Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 5-10